The regulation of digital trade in the TPP: New trade rules for the digital age - GAO, Henry S. (Institutional Knowledge at Singapore Management University, 2018)
With the rapid development of the internet, electronic commerce is also gaining importance in international trade. However, the rules governing digital trade is still largely lacking. While WTO Members have been discussing the regulation of electronic commerce since the last century, little progress has been made. Instead, most of the progresses are made in various free trade agreements, especially those sponsored by the United States. This article starts with a review of the efforts to regulate e-commerce in the WTO, as well as what the pre-TPP US FTAs have achieved so far, followed by a critical appraisal of the achievements and shortcomings of the e-commerce chapter in the TPP. It is hoped that, by reviewing the evolution of the regulation of e-commerce from the WTO to the TPP, we can learn some lessons on how the rules are being shaped, as well as how it might evolve in the future.